An Educational Program According to the Triple Learning Strategy to Develop Some Motor Abilities in the Accuracy of the Skill of Overwhelming Volleyball for the Talented (Journal of Humanities and Social Sciences Research, 2023)
Due to the development of volleyball and its popularity, the followers made the field of training and learning to use the development methods of this game because it depends on the basic foundations in the performance of skills in it, including the development in motor abilities such as flexibility, agility and compatibility in the accuracy of the skill of overwhelming hitting with volleyball for members of the research sample aged 10-17 years The National Center for Volleyball Sports Talent .     Given the importance of kinetic abilities in volleyball, the researcher used the three-way learning strategy method, which makes education more organized, more common and easier, and depends on creating an educational atmosphere that helps the learner to discover the design and application of educational and learning situations to learn the skill and master it.Therefore, the researcher resorted to using this method of learning motor abilities as a method in learning methods and training them in the accuracy of the skill of crushing hitting in volleyball according to the triple learning strategy and the effect of motor abilities to solve the research problem.     As for the research differences, there is a relationship between the pre and post tests for developing motor abilities and the accuracy of the skill of crushing hitting for the members of the research sample.  As the researcher called, the use of educational programs to develop other abilities in different sports activities.